Serum Taurocholic Acid Levels Have Predictive Value for Adverse Maternal and Infant Outcomes in Pregnant Women with Intrahepatic Cholestasis of Pregnancy: A Prospective Cohort Study - Yan Chen; Hong Li; Huanhuan Guo; Junjie Zhou (Clinical and Experimental Obstetrics & Gynecology)
Background: Intrahepatic cholestasis of pregnancy (ICP) is a common liver disorder specific to pregnancy. Taurocholic acid (TCA) has been implicated in the pathogenesis of ICP. This study aimed to investigate the association between serum TCA levels and adverse maternal and infant outcomes in women with ICP. Methods: Pregnant women diagnosed with ICP were categorized into normal or adverse groups based on their pregnancy outcomes. Baseline data, including age, pre-pregnancy body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), and fasting blood sample (5 mL), were collected at 28 weeks of gestation. Serum levels of total bile acid (TBA), alanine transaminase (ALT), aspartate transaminase (AST), total bilirubin (TBIL), and TCA were measured using a fully automatic biochemical analyzer. The predictive value of serum TCA levels for adverse outcomes in ICP was analyzed using receiver operating characteristic (ROC) curve analysis. Subsequently, ICP patients were divided into high and low TCA expression groups, and the changes in baseline data and adverse outcomes were compared between the groups. The relationship between serum TCA levels and adverse outcomes was evaluated using adverse maternal and infant outcome curves. Logistic regression analysis was performed to identify independent risk factors for adverse outcomes in ICP patients. Results: The adverse outcome group showed significant differences in gestational age at delivery (median value of 37 years old, p = 0.0001), levels of TBA (mean ± standard deviation 47.05 ± 6.43 µmol/L, p < 0.0001), ICP severity (proportion of severe ICP patients was 85.14%, p < 0.0001), ALT (mean ± standard deviation 82.59 ± 6.29 U/L, p < 0.0001), AST (median value of 67.50 U/L, p < 0.0001), and TBIL (mean ± standard deviation 47.05 ± 6.99 µmol/L, p < 0.0001), compared to the normal outcome group. Serum TCA levels were higher in the adverse outcome group (mean ± standard deviation 17.79 ± 4.56 µmol/L) than in the normal outcome group (mean ± standard deviation 11.72 ± 3.68 µmol/L) (p < 0.001). Serum taurocholic acid (TCA) levels demonstrated predictive value for adverse outcomes in ICP patients, and the areas under the ROC curve/sensitivity/specificity/cutoff value were 0.8430, 66.22%, 91.03%, and 16.17, respectively. The high TCA expression group had higher levels of TBA (median value of 43.40 µmol/L, p < 0.0001), ALT (median value of 79.89 µmol/L, p < 0.0001), AST (median value of 63.87 µmol/L, p < 0.0001), and TBIL (median value of 43.79 µmol/L, p < 0.0001), a higher proportion of severe ICP cases (71.43%, p < 0.0001). There were a remarkably increased number of adverse pregnancy outcomes (postpartum hemorrhage, premature birth, neonatal asphyxia, fetal distress, amniotic fluid fecal staining, and low birth weight) in the high TCA expression group (n = 49) compared to the low TCA expression group (n = 25) (p < 0.0001). The Kaplan-Meier (KM) curve of patients with high TCA expression shifted to the left compared with patients with low TCA expression (p < 0.0001). The cumulative survival rate of patients with high serum TCA expression (22.22%) was prominently reduced compared to patients with low serum TCA expression (85.03%), indicating that high serum TCA levels increased the risk of maternal and infant adverse outcomes in ICP patients. TBAs, AST, and TCA were identified as independent risk factors for adverse maternal and fetal outcomes in ICP patients. Conclusion: Serum TCA is an independent risk factor for adverse outcomes in ICP patients. Serum TCA levels have predictive values for adverse maternal and infant outcomes in pregnant women with ICP, but there are still some false positives. In clinical diagnosis, it is essential to combine other clinical data to increase the diagnostic accuracy.